INNOVATIVE TECHNOLOGIES IN THE DEVELOPMENT OF THE READING CULTURE OF ECONOMIST STUDENTS IN THE SYSTEM OF HIGHER EDUCATION - Azimova Umidakhan Abdukhaxxarovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the use of innovative technologies to enhance the reading culture of economics students within the framework of Higher Education. Drawing on the rich tapestry of world literature, the study delves into the integration of digital tools and platforms to engage students in meaningful literary experiences. Through a comprehensive analysis of existing literature, the article identifies effective methods, presents results of their application, and discusses implications for the development of a robust reading culture. The study concludes with key insights and practical suggestions for educators and institutions aiming to enrich the academic experience of economics students.